Solvent-Dependent Singlet Fission in Diketopyrrolopyrrole Dimers: A Mediating Charge Transfer versus a Trapping Symmetry-Breaking Charge Separation - Papadopoulos, Ilias; Álvaro-Martins, Maria João; Molina, Desiré; McCosker, Patrick Michael; Keller, Paul A.; Clark, Timothy; Sastre-Santos, Ángela; Guldi, Dirk Michael (Advanced Energy Materials, 2020)
Three diketopyrrolopyrrole (DPP) dimers, linked via different dithienylphenylene spacers, ortho-DPP (o-DPP), meta-DPP (m-DPP), and para-DPP (p-DPP), are synthesized, characterized, and probed in light of intramolecular singlet fission (i-SF). Importantly, the corresponding DPP reference (DPP-Ref) singlet and triplet excited state energies of 2.22 and 1.04 eV, respectively, suggest that i-SF is thermodynamically feasible. The investigations focus on the impact of the relative positioning of the DPPs, and give compelling evidence that solvent polarity and/or spatial overlap govern i-SF dynamics and efficiencies. Polar solvents make the involvement of an intermediate charge transfer (CT) state possible, followed by the population of 1(T1T1) and subsequently (T1 + T1), while spatial overlap drives the mutual interactions between the DPPs. In o-DPP, the correct balance between polar solvents and spatial overlap leads to the highest triplet quantum yield (TQY) of 40%. Notable is the superimposition of CT and triplet excited states, preventing an accurate TQY determination. For m-DPP, poorer spatial overlap correlates with weaker CT character and manifests in a TQY of 11%. Strong CT character acts as a trap and prevents i-SF, as found with p-DPP. The DPP separation is decisive, enabling a symmetry-breaking charge-separated state rather than CT formation, shutting down the formation 1(T1T1).
CRIS-Team Scopus Importer:2020-10-09
Keywords: charge transfer states; diketopyrrolopyrrole dimers; intramolecular singlet fission